Social Representation of Mental Health Disorders in the Italian Big Brother VIP Edition - Rosa Scardigno; Raffaella Gambarrota; Laura Centonze (Behavioral Sciences)
Despite the revolutionary impact of new media, television remains a socially shared reference point for media functions, e.g., information, entertainment, and hybridized genres. Through its simplified knowledge and scripts, television reduces cognitive asymmetry between experts and the public on general and specific topics, thus having a critical role in constructing social representations. This work examines two (apparently) distant realities, i.e., mental health as a fundamental aspect of public health and popular and “light” entertainment formats like reality shows. In the past, researchers investigated media representation of mental illness in general terms alongside other types of programs, e.g., coming-of-age, dramedy television series, and children’s television programs. This study examines how depression is discursively constructed and socially represented in a case that shook the Italian public opinion, i.e., a Big Brother VIP cast member with depression symptoms. The critical discourse analysis, focusing on positioning and representations about depression, enabled us to emphasize that (1) knowledge about depression is poorly defined and participants’ reactions are mostly immature and clumsy, and (2) mass media can play an essential role in creating more mindful and complete knowledge about mental health.